Evaluation of pattern and prognostic factors of head injury cases in a tertiary care centre - Anand, Ashish; Verma, Surender; Garg, Pradeep; Noori, M. Taquedis; Kajal, Ankur; Verma, Anjali (International Surgery Journal, 2020)
Background: Head injury is a major public health problem worldwide and requires appropriate attention both regionally and globally. This study was done to find the patterns and to evaluate prognostic factors for final outcome of cranio-cerebral trauma. Methods: A prospective study of 200 cases of head injury was conducted in a tertiary care hospital during one year duration. Apart from patient’s demographic profile detailed history and examination was recorded. Final outcome of all patients was noted at discharge and during follow up, various prognostic factors were studied by taking Glasgow outcome scale (GOS) at 3 months of head injury. Results: This study included 156 (78%) males and 44 (22%) females with average age of 35.95 years. Assault followed by RTI was the main cause of TBI. The factors which correlated with poor prognosis are presence of increasing age, less GCS at admission, alcohol intoxication and multiple lesions on CT scan. Conclusions: Prognostication of patients with head injury will help to provide timely multimodality approach which will ultimately help in improving outcome of these patients.